2017
DOI: 10.1093/aje/kwx314
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Epidemiological Research Studies in Iran (the PERSIAN Cohort Study): Rationale, Objectives, and Design

Abstract: Noncommunicable diseases (NCDs) account for 76% of deaths in Iran, and this number is on the rise, in parallel with global rates. Many risk factors associated with NCDs are preventable; however, it is first necessary to conduct observational studies to identify relevant risk factors and the most appropriate approach to controlling them. Iran is a multiethnic country; therefore, in 2014 the Ministry of Health and Medical Education launched a nationwide cohort study-Prospective Epidemiological Research Studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
584
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 518 publications
(585 citation statements)
references
References 15 publications
1
584
0
Order By: Relevance
“…The cohort population for each province has been presented in Appendix 1. Other detailed information on the cohort method can be found in the past studies [27,28].…”
Section: Data Source and Variablesmentioning
confidence: 99%
“…The cohort population for each province has been presented in Appendix 1. Other detailed information on the cohort method can be found in the past studies [27,28].…”
Section: Data Source and Variablesmentioning
confidence: 99%
“…In the study, we utilized a subset of data which was collected for Tabari cohort study (TCS). TCS is part of the national cohort, Prospective Epidemiological Research Studies in Iran (PERSIAN) [13,14]. The objective and details of TCS have been explained elsewhere [15].…”
Section: Methodsmentioning
confidence: 99%
“…Data collection method includes structural questionnaire and obtaining blood, urine, hair, and nail samples. The questionnaire used in the study was a standardized questionnaire in which details and features are described in cohort profiles [13,14]. Items of questionnaire consist of general information, socioeconomic status, occupational history, type of fuel used, characteristics of the habitat, life style, history of fertility, history of chronic diseases, drug use, familial history of diseases, oral health, physical examination, physical disabilities, sleep status, physical activity, personal habits (smoking and drinking), food frequency, food supplements, water drink, dietary habits, and exposure to pesticides.…”
Section: Methodsmentioning
confidence: 99%
“…14 One of the major categories of Azar cohort’s questionnaire was about using tobacco and drugs. Other variables in this questionnaire include sex, age, occupation, marital status, education level, disease and medicine use, physical activity, etc.…”
Section: Methodsmentioning
confidence: 99%
“…This study aimed at examining the prevalence and validity of self-reported drug use in the pilot phase of Azar cohort study; a province-level of the Prospective Epidemiological Research Studies of the Iranian adults (PERSIAN) which is a nationwide cohort study launched in 2014. 14 …”
Section: Introductionmentioning
confidence: 99%